Segregation, mobility and encounters in Jerusalem: The role of public transport infrastructure in connecting the 'divided city'. (November 2018) - Rokem, Jonathan; Vaughan, Laura
This paper assesses ways in which urban segregation is shaped and transformed by Jerusalem's public transport network, enhancing mobility and potential group encounters. We suggest that segregation should be understood as an issue of mobility and co-presence in public space, rather than the static residential-based segregation that continues to be a central focus of debate in urban studies. We explore public transport infrastructures, considering how their implementation reflects the variety of ways that transport can have impact: segmenting populations, linking populations and/or creating spaces for interaction or conflict between the city's Jewish Israeli and Arab Palestinian populations. Space syntax network analysis suggests that in the case of Jerusalem, access to public transport is multi-dimensional: as well as providing access to resources, it shapes opportunities for spatial mobility that may either overcome or reinforce area-based housing segregation. We discuss these opportunities in the light of Jerusalem's on-going ethno-national division in an increasingly fractured urban reality.